Role of Phytochemicals in Cancer Chemoprevention: Insights - Blassan P. George; Rahul Chandran; Heidi Abrahamse (MDPI AG, 2021)
Cancer is a condition where the body cells multiply in an uncontrollable manner. Chemoprevention of cancer is a broad term that describes the involvement of external agents to slow down or suppress cancer growth. Synthetic and natural compounds are found useful in cancer chemoprevention. The occurrence of global cancer type varies, depending on many factors such as environmental, lifestyle, genetic etc. Cancer is often preventable in developed countries with advanced treatment modalities, whereas it is a painful death sentence in developing and low-income countries due to the lack of modern therapies and awareness. One best practice to identify cancer control measures is to study the origin and risk factors associated with common types. Based on these factors and the health status of patients, stage, and severity of cancer, type of treatment is decided. Even though there are well-established therapies, cancer still stands as one of the major causes of death and a public health burden globally. Research shows that most cancers can be prevented, treated, or the incidence can be delayed. Phytochemicals from various medicinal plants were reported to reduce various risk factors associated with different types of cancer through their chemopreventive role. This review highlights the role of bioactive compounds or natural products from plants in the chemoprevention of cancer. There are many plant based dietary factors involved in the chemoprevention process. The review discusses the process of carcinogenesis and chemoprevention using plants and phytocompounds, with special reference to five major chemopreventive phytocompounds. The article also summarizes the important chemopreventive mechanisms and signaling molecules involved in the process. Since the role of antioxidants in chemoprevention is inevitable, an insight into plant-based antioxidant compounds that fight against this dreadful disease at various stages of carcinogenesis and disease progression is discussed. This will fill the research gap in search of chemopreventive natural compounds and encourage scientists in clinical trials of anticancer agents from plants.